Dynamics of radiolytic formation of CdSe quantum dots in aqueous solution containing different alcohols: A pulse radiolysis study. (November 2018) - Singh, Avinash; Rath, M.C.
Abstract: The dynamics of radiolytic formation of CdSe quantum dots in aqueous solution containing equimolar ammoniated cadmium sulphate, Cd(NH3 )4 SO4 and sodium selenosulphate, Na2 SeSO3 as precursors for Cd and Se respectively, have been investigated in the presence of different aliphatic alcohols, namely methanol, ethanol, 1-propanol, 2-propanol or 1-butanol by electron pulse radiolysis studies. The mechanism of CdSe quantum dots formation was studied in N2 O saturated aqueous solutions to investigate the formation through reactions with different aliphatic alcohols. The formation of the CdSe quantum dots was found to proceed via the formation of short lived transient intermediate species having and absorption at around 500 nm, which are formed through the reaction of different aliphatic alcohol radicals with the cadmium and selenium precursors. The rate constants for the formation and decay of these intermediate species have been determined. Optical properties of these quantum dots were found to be different in the presence of different alcohols. Highlights: Radiolytic synthesis of CdSe quantum dots were carried out by alcohol radicals. Alcohol radicals were formed in N2 O saturated aqueous solutions. These radicals react with precursors to form transients with absorption at 500 nm. Growth of transient species was slower than that in the case of synthesis by eaq - . Photoluminescence of quantum dots are dependent on alcohols used in the synthesis.